Recent Trends in Social and Behaviour Sciences 2014
DOI: 10.1201/b16658-51
|View full text |Cite
|
Sign up to set email alerts
|

Six key benefits of screencasts in learning Maths: An Irish cas study

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
2
1
Order By: Relevance
“…Gender influences both actual and perceived knowledge where male students reported significantly higher levels of knowledge. The results are contrary to Tunku Ahmad et al (2013) who found gender differences in actual knowledge, but not in perceived knowledge. In addition, discipline of study exerted a significant influence on both knowledge types in favor of noneducation students.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Gender influences both actual and perceived knowledge where male students reported significantly higher levels of knowledge. The results are contrary to Tunku Ahmad et al (2013) who found gender differences in actual knowledge, but not in perceived knowledge. In addition, discipline of study exerted a significant influence on both knowledge types in favor of noneducation students.…”
Section: Discussioncontrasting
confidence: 99%
“…To summarize, objective knowledge is what an individual actually and correctly knows about a given topic, while subjective knowledge refers to what the individual believes he/she knows, which may or may not be correct. Tunku Ahmad, Nordin, and Bello (2013) found a positive correlation of r = 0.53 between objective and subjective knowledge, while others arrived at more moderate figures, such as r = 0.37 (Wirtz & Mattila, 2003). This conclusion indicates that such relationships can be anticipated in future studies.…”
Section: Literature Reviewmentioning
confidence: 76%
“…An attempt to understand the knowledge about GC in Mauritius University by Dookhitram, Narsoo, Sunhaloo, Sukhoo, and Soobron (2013), shows that the students possess moderate knowledge of GC, but their practice of GC in terms of everyday use of computer was not encouraging In a similar study by Ahmad, Nordin and Bello (2013) study on state of GC knowledge among students in a Malaysian public university, the study reported that the student generally lack the knowledge of GC particularly in the area of Energy Star, E-PEAT, Malaysian Green Technology Policy, printer types and energy consumption, energy-efficient practice and hazardous chemical present in computer. Also, the 72 Survey of Education, Engineering, and Information Technology Students' Knowledge of Green Computing in Nigerian University study of Batlegang (2012) on green computing, students, campus computing and the environment in Bostwana revealed a low level of computing knowledge among the university students in Bostwana.…”
Section: Introductionmentioning
confidence: 99%